PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DINAS KEBUDAYAAN PEMUDA DAN OLAHRAGA SERTA PARIWISATA KABUPATEN KARO - Situmorang, Esti Esteria; Simatupang, Sabar LT.; Siregar, Pandapotan Na Uli Sun (JURNAL GLOBAL MANAJEMEN, 2023)
The purpose of this study was to determine the effect of organizational culture and leadership style on employee performance in this type of research is a quantitative study using multiple linear regression methods. The analysis used includes instrumental testing, classical hypothesis testing, and hypothesis testing. The result of this research is the value of Y = -6.784+0.672X1+0.633X2. In a sense, corporate culture has a significant impact on performance. From the t count > t in the table, namely 7,803 > 1,683, with sig 0.000 <0.05, it can be seen that leadership style has a significant effect on performance. 0.000<0.05. Organizational culture and leadership test scores affect performance simultaneously when Fcount > Ftable (62.090 > 4.08) of 0.000 <0.05. Based on the results of testing the coefficient of determinants of organizational culture and leadership style, the adjusted R-square value is 75.8%, meaning that organizational culture and leadership style contribute 75.8% to variations in performance. and other offers 24.2% influenced by other factors not examined in this study.